Oil price volatility, macro-finance interactions and the role of monetary chocks - Algia, Hammami; Samia, Gmidéne (International Journal of Accounting and Economics Studies, 2015)
This paper deals the impact of major external (monetary, financial, Oil supply, aggregate demand) shocks on the real oil price. For this reason, we use the structural VAR methodology (SVAR) on the basis of which we define five structural shock estimate SVAR models to determine the relationship between these five shocks. This paper presents the dynamic effects of these shocks on the real oil price and estimates the estimated contribution of these shocks to real oil price during the M11995– M2 2013 periods. Therefore, the objective of this paper is to identify the structural shocks underlying the real oil price. The results show that financial and monetary chocks are two key determinants of oil prices. The results indicate that the period of financial stress has contributed to the downturn of the economy by boosting the cost of credit and making businesses, households, and financial institutions highly cautious, and consequently to rise of oil price.